Topical and transdermal drug delivery: From simple potions to smart technologies - Benson, Heather; Grice, J.E.; Mohammed, Y.; Namjoshi, S.; Roberts, M.S. (BENTHAM SCIENCE PUBL LTD, 2019)
This overview on skin delivery considers the evolution of the principles of percutaneous absorption and skin products from ancient times to today. Over the ages, it has been recognised that products may be applied to the skin for either local or systemic effects. As our understanding of the anatomy and physiology of the skin has improved, this has facilitated the development of technologies to effectively and quantitatively deliver solutes across this barrier to specific target sites in the skin and beyond. We focus on these technologies and their role in skin delivery today and in the future.